Att förkroppsliga Shakti : en intervjustudie om femininitet i samtida svensk tantra (Aura: Journal for the Study of New Religions, 2022)
In recent years, contemporary tantra, sometimes referred to as “neo-tantra” has spread substantially throughout Sweden. Emphasizing intimacy and polarity as means to healing and liberation, the movement tends to highlight ideals of  “masculine males” and ”feminine females”, while identifying women with Shakti (creativity/immanence) and men with Shiva (consciousness/transcendence). This text examines the use of polarity and more precisely notions of femininity within Swedish contemporary tantra, using qualitative interviews. The purpose is to analyse the relationship between tantric femininity/femininities and the agency and subjectivity of female practitioners. The material is construed from a critical feminist theoretical framework, taking its point of departure in the concept of plural and positional femininities as well as Luce Irigaray’s “sexual difference” (Irigaray 1994) and Rosi Braidotti’s ”nondual materialism” (Braidotti 2011). Irigaray’s position as being one of essentialism is discussed and related to her ventures into yogic and tantric practice. The study suggests that Swedish contemporary tantra in many ways fortifies gender-stereotypical views on femininity while the question of the effects on women’s agency and subjectivity is discussed and left open for further research.